Gametophytic phase of "Doryopteris triphylla" (Pteridaceae, Polypodiopsida). - Seral, Andrea; Gabriel y Galán, José María (Botanica Complutensis, 2016)
Gametophytes of the Pteridaceae are moderately well known but there is still a quite large set of species to describe. Among these is Doryopteris triphylla, a member of the cheilanthoid clade (subgroup hemionitids). The main objective of this work is to describe the gametophyte of D. triphylla. In vitro cultures were prepared with spores coming from various sporophytes of different locations. In vivo observations were done periodically to monitor developmental critical events and reproductive activity. Germination followed the Vittaria pattern and the developmental processes adjusted to the Adiantum type. Adult cordate gametophytes produced normal sexual organs in unisexual prothalli. Doryopteris triphylla gametophytes exhibited somewhat peculiar features: the apical cell divided longitudinally, the first meristematic cell was rectangular, and archegoniate prothalli appeared much before than antheridiate ones.